An Efficient Fair Resource Allocation in Multicast Networks (International Journal of Engineering and Computer Science, 2017)
A decentralized algorithm is presented that enables the different rate-adaptive receivers in different multicast sessions to adjust their rates to satisfy some fairness criterion. The problem of congestion control in networks, which supports both multirate multicast sessions and unicast sessions. A one-bit Explicit Congestion Notification (ECN) marking strategy to be used at the nodes is also proposed. The congestion control mechanism does not require any per-flow state information for unicast flows at the nodes. At the junction nodes of each multicast tree, some state information about the rates along the branches at the node may be required. This Paper calculates the throughput and rates of unicast and multicast packets for the given topology network receivers. The congestion control mechanism takes in to account the diverse user requirements when different receivers within a multicast session have different utility functions, but does not require the network to have any knowledge about the receiver utility functions. This paper compared the performance and fairness of unicast and multicast sessions.